An efficient quantum based routing protocol with local link failure recovery algorithm for manet - Jeni, Jasmine; Juliet, Vimala; Bose, Messiah (International Journal of Engineering and Technology, 2014)
The mobility factor of the nodes in a mobile Ad Hoc networks (MANET) changes the network topology leading to changes in size of the network. As the topology changes, link failure between the nodes takes place due to several reasons like channel interference and dynamic obstacles that give rise to severe performance degradation. Scalability and link failure recovery are the main criteria that will determine the performance of the network in terms of quality of service (QoS). While having different type of nodes, both mobile and immobile, that have several performance severity related to data transfer which is similar to the one in industrial parameter reporting and data logging, there exists a need to overcome performance related issues such as relatively faster and secured data transfer within the set of nodes. We developed the Quantum based Routing protocol (QRP) associated with Local Link Failure Recovery Algorithm (LLFR). The QRP is a routing protocol that uses DSR and AODV as an underlying protocol to improve the QoS in scalable wireless network. The QRP and LLFR establish link failure recovery spontaneously at the point of link breakage. The performance parameters like; packet delivery ratio, throughput, average end to end delay and routing overhead of the routing protocol QRP with LLFR is analyzed using NS2 simulator. Keywords: Ad Hoc Network, Link Failure, Routing Protocols, Scalability, Quality of Service.